Analysis of accidental transmission impacts in the chain «waste management system – public health» - Yevheniia Ziabina; Liliia Khomenko; Evelyn Kumah Osei Owusu (Health Economics and Management Review)
The article summarises arguments and counter-arguments within the scientific debate on the generated waste impact on public health. The main goal of the conducted research is analysis of accidental transmission effects in the chain «waste management system – public health». The systematisation of sources and approaches to solving the problem of waste management system for the population health proved that over 900 publications on the researched topic were cited by in the Web of Science database. At the same time, there are the TOP-5 leading countries in which the problem of the generated waste impact on public health is actively studied: the USA (198 publications), India (107 publications), China (103 publications), England (86 publications), Italy (49 publications). The urgency of solving this scientific problem lies in the fact that in the process of urbanisation and constant industry development, the world waste level is increasing. It provokes a negative impact on the population health. In the article, the analysis of accidental transmission effects in the chain «waste management system – public health» is carried out in the following logical sequence: bibliometric analysis of publications on the researched topic; multiple correlation-regression analysis; check of the built model adequacy using the average approximation error. The conducted research tools were: VOSviewer (an application for producing and visualising bibliometric networks) and MS Excel. The study period was 2000-2019 before the COVID-19 pandemic. Dynamic indicators of the waste volume and disposal, number of the first-time registered disease cases in Ukraine were chosen as the study object. These indicators provide an opportunity to describe significance of the waste management system impact on the population morbidity level. The article presents results of the multiple correlation-regression analysis. It confirmed that with an increase in the waste volume by 1%, the number of the first-time registered disease cases will rise by 0.73%. The study empirically confirms the constructed model adequacy regarding influence of the generated and disposed waste volume and the population health level. The research results can be useful for further scientific activity on this topic.